Dendrimer-transition metal catalyzed oxidation and reduction reactions - Zweni, Pumza P (University of Ottawa (Canada), 2005)
This project was launched with the aim of developing dendrimer catalysts for oxidation and reduction reactions. Poly(amidoamine) (PAMAM) and poly(propyleneimine) (PPI) dendrimers were of interest because of their well-established synthesis. Chapter 1 describes the fundamentals of dendrimers and provides a brief insight of their application in catalysis. In particular, examples of dendritic catalysts that have been previously employed as oxidation and reduction catalysts are presented. Chapter 2 presents the synthesis and characterization of silica-supported PAMAM dendrimers, their phosphomethylation with Ph2 PCH2OH, and their complexation to palladium complexes. Chapter 3 reports the application of the silica-supported PAMAM-Pd complexes to the oxidation of alkenes to methyl ketones under Wacker-type conditions as well as the use of tBuOOH as the oxidant in these reactions. Chapter 4 discusses the use of the above-mentioned complexes to catalyze the selective hydrogenation of dienes to monoolefins in the presence of H2 under mild reaction conditions. Chapter 5 presents our efforts in modifying PPI dendrimers with the salen moiety to give ligands that are coordinated to the metals Ti and V. Attempts at using the former complexes to promote the epoxidation of alkenes and the latter complexes to catalyze the epoxidation of olefinic alcohols are discussed.
Keywords: Chemistry, Organic.